Method for preparing white carbon black and co-producing calcium fluoride from fluorine-containing silica gel
By reacting fluorine-containing silicone with NaOH solution and CaO powder under ultrasonic shock, and mixing it with H2SO4 solution with a spray reactor, the problem of fluorine-containing silicone treatment in the phosphoric acid production process is solved, and resource recovery and efficient preparation of white carbon black are achieved. , reduces energy consumption and safety risks, and meets the production needs of high-purity white carbon black and calcium fluoride.
Patent Information
- Application Number
- CN202411283924.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
In the prior art, fluorine-containing silicone produced during the phosphoric acid production process is difficult to deal with, and poses safety and environmental risks. It is low efficiency and energy consumption when using NH4F as a dissolving agent, and the ammonia recovery device is invested in a large amount, which poses a risk of ammonia leakage.
Add fluorine-containing silicone to NaOH solution and ultrasonic shock reaction to form a water glass solution. Then add CaO powder or Ca(OH)2 to form CaF2 precipitation, and mix it with H2SO4 solution through a spray reactor to separate SiO2 solid powder, and finally pass through pressure Filtration and drying to obtain white carbon black and CaF2 and Na2SiF6 are recovered.
The resource recycling and utilization of fluorine-containing silicone has been realized, the reaction efficiency has been improved, the particle size of SiO2 is reduced, the activity of white carbon black is enhanced, the equipment investment and energy consumption is reduced, and the safety risks is reduced, and the ammonia recovery and evaporation device is required. No wastewater or waste residue is generated.
Smart Images

Figure CN119143166A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wet-process phosphoric acid byproduct treatment, and in particular to a method for preparing white carbon black and co-producing calcium fluoride using fluorine-containing silica gel. Background Art
[0002] Phosphoric acid is an important basic raw material for the production of phosphate fertilizers. During the production of phosphoric acid, F and Si exist in the form of HF, H2SiF6 and SiO2. Fluorine-containing silica gel comes from the absorption of fluorine-containing gases during the production of phosphoric acid and the production of fluoride from by-product fluorosilicic acid. The main component is SiO2, which is produced and separated from the fluorine solution. HF liquid, H2SiF6 liquid and dihydrate crystals H2SiF6·2H2O in the fluorine solution adhere to the surface of SiO2 particles and the pores formed by SiO2 agglomeration, making it very difficult for fluorine-containing silica gel to separate SiO2 and HF and H2SiF6, becoming solid waste with no economic value. It can only be piled up on land, causing environmental pressure. Therefore, it is necessary to develop a treatment technology for fluorine-containing silica gel, and a large number of application technologies are disclosed in the prior art.
[0003] CN1036746A discloses a "new process for producing white carbon black using silica sand", which uses silica sand with a SiO2 content of not less than 99% to react with ammonium fluoride to generate ammonium fluorosilicate, which is then precipitated with 25% to 28% ammonia water, filtered, washed, dried, and crushed to obtain a white carbon black product. CN1092790A discloses a "process for producing high-strengthening white carbon black using fluorine-containing silica gel", which uses waste silica gel produced as a byproduct of calcium phosphate fertilizer as raw material, dissolves it in an ammonium fluoride solution, heats and boils it to generate an ammonium fluorosilicate solution, and then adds 10% to 30% ammonia water to precipitate silicon dioxide, which is then filtered, washed, and dried to obtain a silica product with a specific surface area of 100m 2 / g~250m 2 / g of white carbon black product. CN101462726A discloses a method for preparing white carbon black from fluorinated silica gel. In a dissolving kettle with a stirring and heating device, the fluorinated silica gel is reacted with an ammonium fluoride solution to generate an ammonium fluorosilicate solution. The ammonium fluorosilicate solution is precipitated with ammonia in three stages. The generated white carbon black slurry is pumped into an aging tank for aging, and then filtered and washed six times in countercurrent, the sixth time with clean water; part of the ammonium fluoride solution is separated from the filtrate to recover the ammonium fluoride, and the remaining filtrate and a washing liquid are returned to the system to dissolve the fluorinated silica gel. The filter cake is dried to obtain white carbon black. CN101462732A discloses a method for preparing sodium silicate from fluorinated silica gel. The fluorinated silica gel is dissolved and precipitated by ammoniation to prepare active silicon dioxide; the active silicon dioxide is then reacted with a strong base to prepare a sodium silicate product with a modulus of 2.2 to 3.6.
[0004] Although the existing patented technology can make silica sand or fluorine-containing silica gel into white carbon black and sodium silicate, it uses NH4F as a dissolving agent, which has a high dissolution temperature and low efficiency. In order to deal with the ammonia released during the dissolution process, an ammonia recovery device needs to be added, which requires a large investment in equipment and has the risk of ammonia leakage. In addition, when using ammonia water for precipitation, a large amount of water is brought into the system along with the ammonia water. Whether it is preparing white carbon black or recovering fluorine, the water needs to be evaporated, which consumes a lot of energy.
[0005] CN105036144A discloses a method for preparing highly dispersed white carbon black from acidic fluorine-containing silicon slag. The acidic fluorine-containing silicon slag is first mixed with sodium hydroxide and subjected to microwave treatment. A surfactant is added to the liquid after solid-liquid separation, and then acid is added for aging. The solid is dried to obtain highly dispersed white carbon black. The specific surfactant is not disclosed. On the other hand, it is not explained how to deal with the untreated solid and the liquid containing the surfactant after solid-liquid separation, which poses an environmental risk. Summary of the invention
[0006] The present invention provides a method for preparing white carbon black and co-producing calcium fluoride from fluorine-containing silica gel, which solves the problems in the background technology that by-products in the production process are difficult to handle or have high handling costs and present safety or environmental risks.
[0007] The scheme of the present invention is:
[0008] A method for preparing white carbon black and co-producing calcium fluoride by using fluorine-containing silica gel, characterized in that it comprises the following steps:
[0009] Step 1), adding fluorinated silica gel into a NaOH solution, reacting under ultrasonic vibration to generate a water glass solution;
[0010] Step 2), adding CaO powder or Ca(OH)2 solution to the water glass solution in step 1), and mixing evenly;
[0011] Step 3), filtering the reactants in step 2) to obtain CaF2 precipitate and post-reaction solution A;
[0012] Step 4), spraying the reaction solution A described in step 3) with the H2SO4 solution through a spray reactor, and obtaining SiO2 solid powder and the reaction solution B after solid-liquid separation;
[0013] Step 5), further filtering and drying the SiO2 solid powder to obtain the main product white carbon black;
[0014] Step 6), washing the CaF2 precipitate described in step 3) with water and then drying to obtain co-produced CaF2;
[0015] Step 7), the filtrate after the pressure filtration in step 5) and the solution B after the reaction are used to prepare Na2SiF6.
[0016] As a preferred technical solution, the SiO2 content of the fluorine-containing silica gel in step 1) is 60% to 90%, and the F content is 10% to 15%; the mass concentration of the NaOH solution is 20% to 45%, and the mass ratio of the fluorine-containing silica gel to the NaOH solution is 1:1 to 10.
[0017] As a preferred technical solution, in step 1), the water bath temperature under ultrasonic oscillation is 70° C. to 90° C., the reaction time is 40 min to 120 min, and the ultrasonic oscillation frequency is 200 kHz to 400 kHz.
[0018] As a preferred technical solution, the CaO powder in step 2) has a purity of 80% to 99.9%, the Ca(OH)2 solution has a mass concentration of 0.1% to 1%, and is added in a molar ratio of Ca:F = 0.9 to 1.1:2.
[0019] As a preferred technical solution, the mass concentration of the H2SO4 solution in step 4) is 30% to 40%, the spray rate of the water glass solution is 1 mL / min to 4 ml / min, and the spray rate of the H2SO4 solution is 2 mL / min to 5 ml / min.
[0020] As a preferred technical solution, the drying temperature is 40°C to 100°C, and the drying time is 60min to 150min.
[0021] Reaction mechanism:
[0022] In the first step, SiO2, the main component of fluorinated silica gel, reacts with NaOH to generate NaSiO3 solution, as shown in reaction formula (1):
[0023] SiO2+2NaOH=Na2SiO3+H2O (1)
[0024] The second step is to add CaO or Ca(OH)2, Ca 2+ It reacts with F- in HF to generate CaF2 precipitate which is filtered and separated, as shown in reaction formula (2):
[0025] Ca 2+ +2F - =CaF2 (2)
[0026] The third step is to add H2SO4 to the filtered Na2SiO3 solution to generate white carbon black solid precipitation, and the filtered Na2SO4 solution is used as a standby, as shown in reaction formula (3):
[0027] Na2SiO3+H2SO4=Na2SO4+SiO2+H2O (3)
[0028] In the fourth step, after the Na2SO4 solution is filtered and prepared, the by-product fluorosilicic acid in the wet process phosphoric acid production reacts to generate Na2SiF6, as shown in reaction formula (4):
[0029] Na2SO4+H2SiF6=Na2SiF6+H2SO4 (4)
[0030] Advantages of the present invention:
[0031] 1. The raw material of the present invention is fluorinated silica gel, which is waste residue generated in the production process of phosphoric acid and phosphate fertilizer. The silicon and fluorine resources in the fluorinated silica gel are fully recycled to achieve comprehensive utilization of phosphorus chemical waste residue;
[0032] 2. The present invention disperses the fluorinated silica gel by ultrasonic vibration, increases the contact area between the fluorinated silica gel and the NaOH solvent, and increases the mass transfer rate from the solid phase to the liquid phase, thereby greatly improving the reaction efficiency;
[0033] 3. The present invention allows the water glass solution and the H2SO4 solution to react fully and quickly through the spray reaction, thereby reducing the particle size of the generated SiO2, increasing the specific surface area, and enhancing the activity of the product;
[0034] 4. The present invention not only converts the poorly active fluorine-containing silica gel into highly active white carbon black, but also recycles a large amount of F contained in the fluorine-containing silica gel and converts it into a high-value CaF2 product.
[0035] 5. The Na2SO4 solution produced in the process of the present invention is grafted into the phosphoric acid industry and the H2SiF6 process for preparing Na2SiF6, without generating waste water or waste residue.
[0036] 6. The present invention does not require an ammonia recovery and evaporation device, has a small equipment investment, low safety risk, and low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0038] The present invention provides a method for preparing white carbon black and co-producing calcium fluoride by using fluorine-containing silica gel to solve the problems in the above-mentioned background technology.
[0039] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.
[0040] Example 1
[0041] 100g of fluorinated silica gel with SiO2 content of 87.2% and F content of 10.5% was added to 200ml of NaOH solution with a mass concentration of 25%, and reacted for 60min at a water bath temperature of 70℃ and an oscillation frequency of 200kHz to generate a water glass solution. 65g of CaO powder with a purity of 99.0% was added to the water glass solution, mixed evenly, and reacted for 10min.
[0042] The reactants are filtered and separated to generate CaF2 precipitate and residual water glass solution after the reaction. The residual water glass solution is reacted with H2SO4 with a mass concentration of 40% at a spray rate of 3ml / min through a spray reactor at a spray rate of 2ml / min. After the reaction, solid-liquid separation is performed to obtain SiO2 solid powder and Na2SO4 solution after the reaction. The Na2SO4 solution is exported to wet-process phosphoric acid production enterprises and prepared into a solution with a mass concentration of 20% to 40%. The Na2SiF6 product is produced by reacting at a molar ratio of Na2SO4:H2SiF6=1:1.
[0043] The SiO2 solid powder is further filtered and dried at 60°C for 200 minutes to obtain the main product white carbon black; the CaF2 precipitate is washed with water and dried at 80°C for 100 minutes to obtain the co-product CaF2.
[0044] Comparative Example 1
[0045] The only difference from Example 1 is that the ultrasonic oscillation and spray reaction process are eliminated. Specifically:
[0046] 100g of fluorine-containing silica gel with a SiO2 content of 87.2% and a F content of 10.5% is added to 200ml of a NaOH solution with a mass concentration of 25%, and the mixture is reacted at a water bath temperature of 70°C for 60min to generate a water glass solution; 65g of CaO powder with a purity of 99.0% is added to the water glass solution to generate a CaF2 precipitate; 1500g of H2SO4 with a mass concentration of 40% is added to the remaining water glass solution to generate a SiO2 precipitate and a Na2SO4 solution; the SiO2 precipitate is filtered and dried at 60°C for 200min to obtain the main product white carbon black; the CaF2 precipitate is washed with water and then dried at 80°C for 100min to obtain the co-product CaF2.
[0047] Table 1 Properties of white carbon black obtained in this example
[0048]
[0049] Table 2 Chemical composition of CaF2 obtained in this example
[0050]
[0051] Example 2
[0052] 100g of fluorine-containing silica gel with a SiO2 content of 87.2% and a F content of 10.5% is added to 300ml of a NaOH solution with a mass concentration of 20%, and reacted for 40min at a water bath temperature of 80°C and an oscillation frequency of 300kHz to generate a water glass solution; 65g of CaO powder with a purity of 99.0% is added to the water glass solution to generate a CaF2 precipitate; the remaining water glass solution is reacted with H2SO4 with a mass concentration of 30% at a spray rate of 2ml / min through a spray reactor at a spray rate of 1ml / min to obtain a mixed solution of SiO2 solid powder and Na2SO4; the mixed solution of SiO2 solid powder and Na2SO4 is filtered and dried at 80°C for 150min to obtain the main product white carbon black; the CaF2 precipitate is washed with water and then dried at 100°C for 60min to obtain the co-product CaF2.
[0053] Comparative Example 2
[0054] The only difference from Example 2 is that the ultrasonic oscillation and spray reaction process are eliminated. Specifically:
[0055] 100g of fluorine-containing silica gel with a SiO2 content of 87.2% and a F content of 10.5% is added to 300ml of a NaOH solution with a mass concentration of 20%, and the mixture is reacted at a water bath temperature of 80°C for 40min to generate a water glass solution; 65g of CaO powder with a purity of 99.0% is added to the water glass solution to generate a CaF2 precipitate; 1600g of H2SO4 with a mass concentration of 35% is added to the remaining water glass solution to generate a SiO2 precipitate and a Na2SO4 solution; the SiO2 precipitate is filtered and dried at 80°C for 150min to obtain the main product white carbon black; the CaF2 precipitate is washed with water and then dried at 100°C for 60min to obtain the co-product CaF2.
[0056] Table 3 Properties of white carbon black obtained in this example
[0057]
[0058] Table 4 Chemical composition of CaF2 obtained in this example
[0059]
[0060] Example 3
[0061] 100g of fluorine-containing silica gel with a SiO2 content of 87.2% and a F content of 10.5% is added to 200ml of a NaOH solution with a mass concentration of 40%, and reacted for 120min at a water bath temperature of 60°C and an oscillation frequency of 400kHz to generate a water glass solution; 65g of CaO powder with a purity of 99.0% is added to the water glass solution to generate a CaF2 precipitate; the remaining water glass solution is reacted with H2SO4 with a mass concentration of 25% at a spray rate of 2ml / min through a spray reactor at a spray rate of 4ml / min to generate a mixed solution of SiO2 solid powder and Na2SO4; Step 5, filtering the mixed solution of SiO2 solid powder and Na2SO4 and drying it at 80°C for 120min to obtain the main product white carbon black; the CaF2 precipitate is washed with water and then dried at 120°C for 60min to obtain the co-product CaF2.
[0062] Comparative Example 3
[0063] 100g of fluorine-containing silica gel with a SiO2 content of 87.2% and a F content of 10.5% is added to 200ml of a NaOH solution with a mass concentration of 40%, and the mixture is reacted at a water bath temperature of 60°C for 120min to generate a water glass solution; 65g of CaO powder with a purity of 99.0% is added to the water glass solution to generate a CaF2 precipitate; 1800g of H2SO4 with a mass concentration of 25% is added to the remaining water glass solution to generate a SiO2 precipitate and a Na2SO4 solution; the SiO2 precipitate is filtered and dried at 80°C for 120min to obtain the main product white carbon black; the CaF2 precipitate is washed with water and then dried at 120°C for 60min to obtain the co-product CaF2.
[0064] Table 5 Properties of white carbon black obtained in this example
[0065]
[0066] Table 6 Chemical composition of CaF2 obtained in this example
[0067]
[0068] The product white carbon black has high purity and large specific surface area, and can be used as a high-quality defluorination agent in the production process of wet-process phosphoric acid. The calcium fluoride product has high purity and meets the requirements of GB / T 27804-2011 calcium fluoride qualified products.
[0069] Example 4
[0070] 100g of fluorinated silica gel with SiO2 content of 85.3% and F content of 12.3% was added to 200ml of NaOH solution with a mass concentration of 25%, and reacted for 60min at a water bath temperature of 70℃ and an oscillation frequency of 200kHz to generate a water glass solution. A Ca(OH)2 solution with a mass concentration of 0.5% was added to the water glass solution, and the molar ratio of Ca:F in the reactants was 1.1:2, and the mixture was mixed evenly and reacted for 10min.
[0071] The reactants were filtered and separated to generate CaF2 precipitate and residual water glass solution after the reaction. The residual water glass solution was reacted with H2SO4 with a mass concentration of 40% at a spray rate of 3ml / min through a spray reactor at a spray rate of 2ml / min, and after the reaction, solid-liquid separation was performed to obtain SiO2 solid powder and Na2SO4 solution after the reaction.
[0072] The SiO2 solid powder is further filtered and dried at 60°C for 200 minutes to obtain the main product white carbon black; the CaF2 precipitate is washed with water and dried at 80°C for 100 minutes to obtain the co-product CaF2.
[0073] Example 5
[0074] 100g of fluorinated silica gel with SiO2 content of 86.2% and F content of 11.5% was added to 200ml of NaOH solution with a mass concentration of 25%, and reacted for 60min at a water bath temperature of 70℃ and an oscillation frequency of 200kHz to generate a water glass solution. 65g of CaO powder with a purity of 99.0% was added to the water glass solution, mixed evenly, and reacted for 10min.
[0075] The reactants were filtered and separated to generate CaF2 precipitate and residual water glass solution after the reaction. The residual water glass solution was reacted with H2SO4 with a mass concentration of 40% at a spray rate of 3ml / min through a spray reactor at a spray rate of 2ml / min, and after the reaction, solid-liquid separation was performed to obtain SiO2 solid powder and Na2SO4 solution after the reaction.
[0076] The SiO2 solid powder is further filtered and dried at 60°C for 200 minutes to obtain the main product white carbon black; the CaF2 precipitate is washed with water and dried at 80°C for 100 minutes to obtain the co-product CaF2.
[0077] Example 6
[0078] 100g of fluorinated silica gel with a SiO2 content of 84.8% and a F content of 12.5% is added to 300ml of a NaOH solution with a mass concentration of 20%, and reacted for 40min at a water bath temperature of 80°C and an oscillation frequency of 300kHz to generate a water glass solution; a Ca(OH)2 solution with a mass concentration of 0.5% is added to the water glass solution, and the Ca:F molar ratio in the reactants is 1:2 to generate a CaF2 precipitate; the remaining water glass solution is reacted with a H2SO4 with a mass concentration of 30% at a spray rate of 2ml / min through a spray reactor at a spray rate of 1ml / min to obtain a mixed solution of SiO2 solid powder and Na2SO4; the mixed solution of SiO2 solid powder and Na2SO4 is filtered and dried at 80°C for 150min to obtain the main product white carbon black; the CaF2 precipitate is washed with water and then dried at 100°C for 60min to obtain the co-product CaF2.
[0079] Table 7 Properties of white carbon black obtained in Examples 4-6
[0080]
[0081] Table 8 Chemical composition of CaF2 obtained in Examples 4-6
[0082]
[0083] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing white carbon black and co-producing calcium fluoride by using fluorinated silica gel, characterized in that: The following steps are involved: Step 1), adding fluorinated silica gel into a NaOH solution, reacting under ultrasonic vibration to generate a water glass solution; Step 2), adding CaO powder or Ca(OH)2 solution to the water glass solution in step 1), and mixing well; Step 3), filtering the reactants in step 2) to obtain CaF2 precipitate and post-reaction solution A; Step 4), spraying the reaction solution A described in step 3) with the H2SO4 solution through a spray reactor, and obtaining SiO2 solid powder and the reaction solution B after solid-liquid separation; Step 5), further filtering and drying the SiO2 solid powder to obtain the main product white carbon black; Step 6), washing the CaF2 precipitate described in step 3) with water and then drying to obtain co-produced CaF2; Step 7), the filtrate after the pressure filtration in step 5) and the solution B after the reaction are used to prepare Na2SiF6.
2. A method for preparing white carbon black and co-producing calcium fluoride by using fluorine-containing silica gel as claimed in claim 1, characterized in that: The SiO2 content of the fluorine-containing silica gel in step 1) is 60% to 90%, and the F content is 10% to 15%; the mass concentration of the NaOH solution is 20% to 45%, and the mass ratio of the fluorine-containing silica gel to the NaOH solution is 1:1 to 10.
3. A method for preparing white carbon black and co-producing calcium fluoride by using fluorine-containing silica gel as claimed in claim 1, characterized in that: In step 1), the water bath temperature under ultrasonic oscillation is 70° C. to 90° C., the reaction time is 40 min to 120 min, and the ultrasonic oscillation frequency is 200 kHz to 400 kHz.
4. A method for preparing white carbon black and co-producing calcium fluoride by using fluorine-containing silica gel as claimed in claim 1, characterized in that: The purity of the CaO powder in step 2) is 80% to 99.9%, the mass concentration of the Ca(OH)2 solution is 0.1% to 1%, and it is added at a molar ratio of Ca:F=0.9 to 1.1:
2.
5. A method for preparing white carbon black and co-producing calcium fluoride by using fluorine-containing silica gel as claimed in claim 1, characterized in that: The mass concentration of the H2SO4 solution in step 4) is 30% to 40%, the spray rate of the water glass solution is 1 mL / min to 4 ml / min, and the spray rate of the H2SO4 solution is 2 mL / min to 5 ml / min.
6. A method for preparing white carbon black and co-producing calcium fluoride by using fluorine-containing silica gel as claimed in claim 1, characterized in that: The drying temperature is 40° C. to 100° C., and the drying time is 60 min to 150 min.
Citation Information
Patent Citations
Method for preparing white carbon black from fluorine-containing silica gel
CN101462726A
Method for preparing sodium silicate from fluorine-containing silica gel
CN101462732A
Process of producing white carbon using siliceous sand
CN1036746A
Method for using acidic fluorine-containing silicon slag to prepare highly dispersable white carbon black
CN105036144A
Process for preparing high strengthening silica white from fluorine-contg. silica gel
CN1092790A
Cited By
Method for preparing lithium battery negative electrode material by using phosphate fertilizer solid waste and application of lithium battery negative electrode material
CN121536938A
